Analisis Peran Informasi Akuntansi dalam Sistem Pengendalian Manajemen Lembaga Keuangan Mikro - Dwi Mutia Amiati; Elin Erlina Sasanti; Adhitya Bayu Suryantara (Universitas Galuh, 2023)
This study aims to determine the role of accounting information in the management control system that occurs in an organization, namely the LKM BUMDes Bina Sejahtera. The research approach used is descriptive qualitative, which provides a systematic description of the role of accounting information in the management control system of LKM Bina Sejahtera. The data analysis technique used is an explanation written in a narrative related to the management control system and the use of accounting information at the LKM Bina Sejahtera. The results showed that the LKM of Bina Sejahtera had a sound management control system, although not perfect, and use of accounting information as a basis for decision-making and evaluation.